The sustainable development like new environmental - Antúnez Sánchez, Alcides (2018)
An analysis at the beginning of the sustainable development like new environmental knowledge, for the need plucks up the juridical environmental formation like policy of the Public Administration in special of the Universities in the essay, as from that the man in his relation with nature and in order to achieve the conservation of the environmental conditions that calls for for his habitat, without prejudice to development the economic activities that have impact on it, needs to know like establishing mechanisms, measures and procedures that they enable a harmonious cohabitation of a natural, of it social and of what's economic. The environmental subjects have earned prominence in the arguments in the international company, including States' lectures, the academic forums and the media. You are spoken to of global warming; Nevertheless, the scientists correct and emphasize in using the adequate term: “Climatic change”. You set for yourself as objective, demonstrating the need of the juridical environmental formation at the Universities, that it allow attaining the sustainable development within the States' as good as new public policies to taste environmental. The methods of analysis are utilized synthesis, induction deduction, and juridical comparison.